2021
DOI: 10.3390/ani11123588
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Resveratrol Supplementation on Growth Performance and Anti-Inflammatory Ability in Ducks (Anas platyrhynchos) through the Nrf2/HO-1 and TLR4/NF-κB Signaling Pathways

Abstract: The aim of this study was to explore the effect of dietary resveratrol on the growth performance and anti-inflammatory mechanism in ducks. A total of 280 one-day-old specific pathogen-free male ducklings (Anas platyrhynchos) with an average body weight of 35 ± 1 g were randomly divided into two dietary treatment groups with different supplementation levels of resveratrol for growth performance experiments: R0 and R400 (0 and, 400 mg kg−1 resveratrol, respectively). At the age of 28 days, 16 ducks were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 58 publications
2
16
0
Order By: Relevance
“…Zhang et al [ 11 ] revealed that the mRNA expression levels of CAT , GR , MnSOD , HO-1, and Nrf2 in the spleen of broilers under HS were increased by dietary RES, indicating that the Nrf2 signaling pathway in the spleen might be activated. Similarly, Wang et al [ 17 ] reported that Nrf2 and SOD mRNA levels in the jejunum of heat-stressed boilers could be improved by RES, which may alleviate the inhibitory effect of HS on the Nrf2 signaling pathway. The present study found that Nrf2 , HO-1 , and NQO1 mRNA in the muscle of heat-stressed broilers were remarkably improved by RES.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [ 11 ] revealed that the mRNA expression levels of CAT , GR , MnSOD , HO-1, and Nrf2 in the spleen of broilers under HS were increased by dietary RES, indicating that the Nrf2 signaling pathway in the spleen might be activated. Similarly, Wang et al [ 17 ] reported that Nrf2 and SOD mRNA levels in the jejunum of heat-stressed boilers could be improved by RES, which may alleviate the inhibitory effect of HS on the Nrf2 signaling pathway. The present study found that Nrf2 , HO-1 , and NQO1 mRNA in the muscle of heat-stressed broilers were remarkably improved by RES.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our research confirmed that RES could activate the Nrf2 signaling pathway in the spleen [ 11 ] and intestinal tract [ 16 ] of broilers under HS and alleviate the oxidative damage caused by HS. A recent study in ducks revealed that RES could alleviate lipopolysaccharide-induced liver peroxidation through the enhanced expression of Nrf2 and HO-1 [ 17 ]. According to the above findings, we hypothesized that RES possibly improves the muscle antioxidant capacity of broilers subjected to HS through Nrf2 signaling pathway activation in muscle tissue, which improves meat quality.…”
Section: Introductionmentioning
confidence: 99%
“…RNA isolation and RT‐qPCR were performed as previously reported 7 . The gene accession numbers of the ducks were obtained from the National Center for Biotechnology Information, and duck gene primers were purchased from Sangon Biotech Co. Ltd (Shanghai, China) (Supporting Information, Table S2).…”
Section: Methodsmentioning
confidence: 99%
“…Lipopolysaccharides (LPS) are the primary pathogenic components of the outer membrane of Gram‐negative bacteria; thus, LPS have become a research focus 4 . Previous studies have indicated that the LPS challenge is linked to a decrease in growth performance, oxidative stress, and inflammatory reactions in animals and humans 5‐7 . In the past century, antibiotics have been recognized as alternative therapeutic agents to combat the reduction in animal growth performance and multiple inflammatory diseases caused by bacterial infections.…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression was normalized to β-actin mRNA levels in each sample and fold change was determined using the comparative method (2 −ΔΔCt ), where Ct is defined as the cycle number at which fluorescence reaches the fixed threshold. 19,20…”
Section: Food and Function Papermentioning
confidence: 99%